Evidence for daily and weekly rhythmicity but not lunar or seasonal rhythmicity of physical activity in a large cohort of individuals from five different countries. (3rd October 2015) - Refinetti, Roberto; Sani, Mamane; Jean-Louis, Girardin; Pandi-Perumal, Seithikurippu R.; Durazo-Arvizu, Ramon A.; Dugas, Lara R.; Kafensztok, Ruth; Bovet, Pascal; Forrester, Terrence E.; Lambert, Estelle V.; Plange-Rhule, Jacob; Luke, Amy
Abstract: Background Biological rhythmicity has been extensively studied in animals for many decades. Although temporal patterns of physical activity have been identified in humans, no large-scale, multi-national study has been published, and no comparison has been attempted of the ubiquity of activity rhythms at different time scales (such as daily, weekly, monthly, and annual). Methods Using individually worn actigraphy devices, physical activity of 2, 328 individuals from five different countries (adults of African descent from Ghana, South Africa, Jamaica, Seychelles, and the United States) was measured for seven consecutive days at different times of the year. Results Analysis for rhythmic patterns identified daily rhythmicity of physical activity in all five of the represented nationalities. Weekly rhythmicity was found in some, but not all, of the nationalities. No significant evidence of lunar rhythmicity or seasonal rhythmicity was found in any of the groups. Conclusions These findings extend previous small-scale observations of daily rhythmicity to a large cohort of individuals from around the world. The findings also confirm the existence of modest weekly rhythmicity but not lunar or seasonal rhythmicity in human activity. These differences in rhythm strength have implications for the management of health hazards of rhythm misalignment. Key Messages: Analysis of the pattern of physical activity of 2, 328 individuals from five countries revealed strong daily rhythmicity in all five countries, moderate weekly rhythmicity in some countries, and no lunar rhythmicity or seasonal rhythmicity in any of the countries.